2022
DOI: 10.1002/jmri.28218
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Survival Outcomes of Patients With LI‐RADS‐M Hepatocellular Carcinomas and Intrahepatic Cholangiocarcinomas

Abstract: Background There is a sparsity of data evaluating outcomes of patients with Liver Imaging Reporting and Data System (LI‐RADS) (LR)‐M lesions. Purpose To compare overall survival (OS) and progression free survival (PFS) between hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (iCCA) meeting LR‐M criteria and to evaluate factors associated with prognosis. Study Type Retrospective. Subjects Patients at risk for HCC with at least one LR‐M lesion with histologic diagnosis, from 8 academic centers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In this issue of JMRI , Kierans et al reported a comparison between clinical outcomes of HCC and iCCA with' LR‐M' features 5 . The hypothesis is that primary liver cancers with similar imaging features may show a similar clinical outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of JMRI , Kierans et al reported a comparison between clinical outcomes of HCC and iCCA with' LR‐M' features 5 . The hypothesis is that primary liver cancers with similar imaging features may show a similar clinical outcome.…”
mentioning
confidence: 99%
“…In this issue of JMRI, Kierans et al reported a comparison between clinical outcomes of HCC and iCCA with' LR-M' features. 5 The hypothesis is that primary liver cancers with similar imaging features may show a similar clinical outcome. Authors retrospectively collected 120 patients with histologically confirmed either HCC (n = 65) and iCCA (n = 55) from eight centers.…”
mentioning
confidence: 99%